Universities in Transition Foregrounding Social Contexts of Knowledge in the First Year Experience - Brook, Heather (University of Adelaide Press, 2014)
By recasting 'the transition to university' as simultaneously and necessarily entailing a transition of university - indeed universities - and of their many and varied constitutive relations, structures and practices, the contributors to this book seek to reconceptualise the 'first-year experience' in terms of multiple and dynamic processes of dialogue and exchange amongst all participants. They interrogate taken-for-granted understandings of what 'the university' is, and consider what universities might yet become.